เสน่ห์ในความไม่สมบรูณ์ของเทคนิคโรโตสโคปแอนิเมชัน - พันธะพจน์ นิจจัง (Fine Arts Journal: Srinakharinwirot University, 2018)
2D animator always focuses on creating their own animation to create a unique and distinctive work. Meanwhile, the rotoscope animation starting from a mimic of motion pictures from a frame by frame. Then put them together to become another type of animation. This is a devastating effect or a reduction in the value of work that an animator tries to avoid. There will be any way to add value or create aesthetics to the rotoscope technique. Equivalent to the classic two-dimensional animation. This article will discuss techniques to create fascination in the work. For applied to making a film, music video or other types of work.